셀룰라제와 파파인을 이용한 키토산 섬유의 효소가수분해 - 이소희; So Hee Lee; 김혜림; Hye Rim Kim; 이범훈; Bum Hoon Lee; 송화순; Wha Soon Song (한국섬유공학회지, 2010)
The enzymatic processing conditions of chitosan nonwoven using cellulase and papain were optimized to determine the correlation between chitosan nonwoven and both enzymes. The hydrolytic activity and structural change in the chitosan fiber were evaluated. Chitosan hydrolysis by cellulase was maximized using 10% (o.w.f.) cellulase at $40^{°}C$ for 30 minutes under pH 5, whereas that by papain was optimized at a papain concentration of 10% (o.w.f.), and $60^{°}C$ for 60 minutes at pH 8. The degree of deacetylation of the chitosan decreased by 3.9% and 2.4% using cellulase and papain, respectively, which reduced slightly the level of acid dye adsorption of chitosan. DSC, XRD, FT-IR and GPC analysis confirmed no substantial changes in the molecular and crystalline structures of chitosan by the enzymatic treatment.